The Multifaceted Role of Psyllium Husk in Enhancing Metabolic and Athletic Performance: A Comprehensive Review - Biesiada, Wiktor; Błaszków, Krzysztof; Szydłowska, Sara; Elias, Jagoda; Zubiak, Marlena; Woźniak, Justyna; Kmieć, Justyna Weronika; Piekarska, Ewa (Quality in Sport, 2025)
Introduction Psyllium husk, derived from Plantago ovata seeds, is a key dietary fiber with benefits for metabolism and athletic performance. This review examines its role in glycemic control, lipid metabolism, gut microbiota, inflammation, and sports nutrition. Its gel-forming properties aid nutrient absorption and energy management, positioning it as a tool for addressing metabolic disorders and improving physical performance. Recent studies highlight its potential for endurance, recovery, and weight management, while emphasizing the need for further research into personalized applications. Purpose of the Work: This review consolidates findings on psyllium’s benefits for metabolic health and sports performance, offering insights for future research and practical use. Materials and Methods: A systematic review was conducted using databases including PubMed, Scopus, and Google Scholar. Search terms included psyllium husk, dietary fiber, metabolic health, sports performance, glycemic control, lipid metabolism, gut microbiota, precision nutrition. Relevant studies were synthesized to compile findings. Results: Psyllium husk offers significant metabolic health benefits. Clinical trials report improved glycemic control, with reductions in postprandial glucose and HbA1c through slowed carbohydrate absorption and enhanced insulin sensitivity. Its lipid-lowering effects, particularly on LDL cholesterol, reduce cardiovascular risk, supporting its role in managing dyslipidemia. Psyllium’s prebiotic properties enhance gut microbiota by increasing beneficial bacteria and SCFAs like butyrate, improving glucose metabolism, gut barrier function, and reducing inflammation. Anti-inflammatory effects include lowered CRP and cytokines, beneficial in conditions like metabolic syndrome. In sports, psyllium aids endurance and recovery by stabilizing glucose levels and mitigating gastrointestinal distress, demonstrating its versatility for health and performance optimization.